The Department of Social Medicine at Montefiore and Vic Sidel - Roberto Belmar (Social Medicine Publication Group, 2013)
Montefiore's Division of Social Medicine (DSM) (later a Department) was conceived and created by Martin Cherkasky, MD, in 1950 shortly before Cherkasky became the Director of Montefiore Hospital. As DSM's first Chairman, Cherkasky understood health care as a social endeavor. The Department not only delivered first-class medical and health care, but understood the individual, the family, and the community as social entities involved in the creation of a more just and egalitarian society.